The medieval Internet : power, politics and participation in the digital age - Jensen, Jakob Linaa (Emerald Publishing Limited, 2020)
This book sheds light on the world of the Internet and social media and their relationship with surveillance and control, through a historical prism drawn from the Medieval Age.